HUBUNGAN PENGETAHUAN DAN PARITAS IBU DENGAN PENGGUNAAN KB SUNTIK DI PMB ZUNIAWATI PALEMBANG TAHUN 2021 - Nurbaity; Dona Trisundari (LPPM STIKes Mitra Adiguna, 2023)
WHO data shows that there are as many as 159 million IUD users, 23 million implant contraceptive users, 74 million injectable birth control users, 150 million pill contraceptive users. Family planning is one of the most basic and primary health services for women. The use of injectable birth control can be caused by several factors including the mother's knowledge and parity. The injection contraceptive method is the most widely used contraceptive method. The aim of the study was to find out the relationship between knowledge and maternal parity with the use of injectable family planning at PMB Zuniawati Palembang in 2021. The research method used a cross sectional method. The population in this study were all 1-month, 2-month and 3-month injectable family planning acceptors who visited PMB Zuniawati Palembang during the study with a total sample of 35 respondents. The results showed that the frequency distribution of respondents mostly used 3-month injection contraception as many as 16 respondents (45.7%), most of them had good knowledge as many as 23 respondents (65.7%), most of them were multiparous as many as 20 respondents (57.1%) . The results of the statistical test found that there was a significant relationship between knowledge (p value = 0.039) and maternal parity (p value = 0.045) with the use of injectable family planning at PMB Zuniawati Palembang in 2021 with value. Suggestions are that it is hoped that health workers can further improve the provision of counseling to family planning acceptors to increase acceptors' knowledge about the contraceptives used, especially injectable contraceptives.